Associative Transcriptomics Study Dissects the Genetic Architecture of Seed Glucosinolate Content in Brassica napus - Lu, Guangyuan (DNA Res, 2014)
Breeding new varieties with low seed glucosinolate (GS) concentrations has long been a prime target in Brassica napus. In this study, a novel association mapping methodology termed ‘associative transcriptomics’ (AT) was applied to a panel of 101 B. napus lines to define genetic regions and also candidate genes controlling total seed GS contents. Over 100,000 informative single-nucleotide polymorphisms (SNPs) and gene expression markers (GEMs) were developed for AT analysis, which led to the identification of 10 SNP and 7 GEM association peaks. Within these peaks, 26 genes were inferred to be involved in GS biosynthesis. A weighted gene co-expression network analysis provided additional 40 candidate genes. The transcript abundance in leaves of two candidate genes, BnaA.GTR2a located on chromosome A2 and BnaC.HAG3b on C9, was correlated with seed GS content, explaining 18.8 and 16.8% of phenotypic variation, respectively. Resequencing of genomic regions revealed six new SNPs in BnaA.GTR2a and four insertions or deletions in BnaC.HAG3b. These deletion polymorphisms were then successfully converted into polymerase chain reaction–based diagnostic markers that can, due to high linkage disequilibrium observed in these regions of the genome, be used for marker-assisted breeding for low seed GS lines.